Preparação, estudo da estrutura e propriedades físico-químicas de compósitos baseados em poliuretanos termorrígidos e nanotubos de carbono - Magnovaldo Carvalho Lopes (2015)
The present work aimed to the preparation and characterization of polymer nanocomposites produced with a thermoset polyurethane elastomer (PUE) and multiwalled carbon nanotubes (MWCNT) unmodified and modified by acid treatment and isocyanate. The PUE are relevant materiaIs because they are used in many industrialsectors such as electronics, aerospace, automotive and medicine.Thermogravimetric analysis showed that the functionalized MWCNTs(commercial) presented 4.0% of mass loss, which can be attributed to oxygen containing groups. The MWC T modified with isocyanate (MWCNT-NCO) synthesized in this work showed 30.0% of mass loss that is assigned to the isocyanate groups and residual oxygen containing groups. The X-ray photoelectron spectroscopy (XPS) and the high-resolution nuclear magnetic resonance with magic angle spinning(HRMAS NMR) were used to study the oxygenated functions and isocyanates covalently bonded to the surface of MWCNTs.Processes which employ a high shear mixer and mill rolls were employed for the preparation of three different polyurethane composites (PUE) based on MWC Ts dispersed in prepolymer and polyol. The sequence of improvements applied in the three systems was motivated by the need of solving experimental problems such as todecrease the negative influence of moisture in the dispersion of the nanotubes; and improve the quality of the dispersion and interaction of the nanomaterials with the polymer matrix. In the first system, two masterbatches were prepared containing 3.0 and 5.0 wt%of unmodified and oxygenated MWCNTs dispersed, respectively, in the prepolymer. These concentrates were diluted, and resulted in composites with concentrations between 0.25 and 1.0 wt% of MWCNTs. The composites containing 0.5 wt% of oxygenated MWCNT exhibited the best increases of 47.0 and 32.0% in the elastic modulus and tensile strength, respectively, when compared to the PUE. Dynamic mechanical therrnal analysis data (DMTA) showed that both composites, produced from oxygenated and unrnodified MWCNT, showed an increase of about 20°C with respect to the Tg of PUE. In a second system, two concentrates were prepared containing 3.0 wt% of MWCNT unmodified and modified dispersed in polyol. These concentrates resulted, after dilution, in cornposites containing 0.5 wt% of MWCNTs. For the compositecontaining oxygenated MWCNT, were observed gains m the tensile strength and elongation when compared to the PUE. In addition, electrical conductivity values that allow electrostatic dissipation were achieved for these composites. In the case ofthe third system, the MWCNT-NCO were dispersed in the polyol. The composites were prepared directly at the concentrations of 0.25 and 0.5 wt% of MWCNT-NCO for this system. The composite containing 0.25 wt% of MWCNT-NCO presented an increase of 31.0% in the tear strength when compared to PUE. lncreases intensile strength, elongation and tenacity were also observed for this composite. Moreover, the composite containing 0.5 wt% of MWCNT-NCO presented an increase of 9.0% in abrasion when compared to PUE.The nanoindentation technique was used to determine the elastic modulus and hardness in the sub-surface of PUE and the composites prepared with the first and third systems. This is an advanced technique of characterization with nanometer resolution and the results allowed a cornparative analysis with respect to the results of conventional mechanical tests. Optical and electron microscopy data indicated an improved dispersion of the MWCNT-COOH and MWCNT-NCO in the polymer matrix. The studies of the three systems suggest that the increases in thermal and mechanical properties are associatedwith chemical compatibility between matrix and nanotube surfaces. It can be affirrn that this study showed that the covalent modification in surface of MWCNTs and the use of efficient dispersion strategies are essential to optimize the final properties of the composites.